Rational Nonmonotonic Reasoning - Kadie, Carl (Association for Uncertainty in Artificial Intelligence, 1988)
Nonmonotonic reasoning is a pattern of reasoning that allows an agent to make and retract (tentative) conclusions from inconclusive evidence. This paper gives a possible-worlds interpretation of the nonmonotonic reasoning problem based on standard decision theory and the emerging probability logic. The system's central principle is that a tentative conclusion is a decision to make a bet, not an assertion of fact. They system is rational, and as sound as the proof theory of its underlying probability logic.